Risk Assessment for Pulmonary Artery Hypertension in Adult Patient with Uncorrected Atrial Septal Defect by Six-Minute Walk Test and Mean Pulmonary Arterial Pressure - Suryantoro M., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Risk Assessment for Pulmonary Artery Hypertension in Adult Patient with Uncorrected Atrial Septal Defect by Six-Minute Walk Test and Mean Pulmonary Arterial Pressure